Preventive effect of tilapia skin collagen hydrolysates on ulcerative colitis mice based on metabonomic and 16 S rRNA gene sequencing. (27th January 2023) - Chen, Zhaoni; Nong, Yunyuan; Wang, Qianyi; Feng, Linlin; He, Ying; Guo, Bingjian; Qin, Yuelian; Zhong, Xinyu; Qin, Jinghua; Wei, Jinbin; Dong, Min; Pan, Shihan; et al.
Abstract: BACKGROUND: Tilapia skin collagen hydrolysates (TSCHs) are the product of enzymatic hydrolysis of collagen, which is mainly extracted from tilapia skin. The components of TSCHs have recently been reported to play a preventive role in dextran sulfate sodium (DSS)‐induced ulcerative colitis (UC). However, it has not been illustrated whether TSCHs can prevent against DSS‐induced UC via the gut microbiota and its derived metabolites. RESULTS: TSCHs are mainly composed of amino acids, which have similar characteristics to collagen, with most having a molecular weight below 5 kDa. In a mouse model of UC, TSCHs had no toxic effect at a dose of 60 g kg −1 and could reduce body weight changes, colon length, histopathological changes and score, and the level of the serum inflammatory cytokine interleukin (IL)‐6. Concurrently, 16 S rRNA sequencing showed that TSCHs significantly reduced the abundance of Bacteroidetes and Proteobacteria at the phylum level and norank_f__Muribaculaceae and Escherichia‐Shigella at the genus level, while they increased the abundance of Firmicutes at the phylum level and Lachnoclostridium, Allobaculum, Enterorhabdus, and unclassified__f__Ruminococcaceae at the genus level. Target metabolomic analysis showed that TSCHs elevated the concentration of total acid, acetic acid, propanoic acid, and butanoic acid, but reduced isovaleric acid concentrations. Moreover, Pearson correlation analysis revealed that Allobaculum, unclassified_Ruminococcaceae, and Enterorhabdus were positively correlated with acetic acid and butyric acid, but not Escherichia‐Shigella . CONCLUSION: These findings suggest that TSCHs can prevent UC by modulating gut microbial and microbiota‐derived metabolites. © 2023 Society of Chemical Industry.